An Analysis of English Code Mixing Used in Indonesian Magazine - Syafryadin Syafryadin; Haryani Haryani (Universitas Pendidikan Mandalika, 2020)
This study investigated the types of code mixing used in one of teenage magazines in Indonesia, namely Aneka Yess! magazine. The research question was “what types of code mixing used in Aneka Yess! magazine”. The objective of this study was to find out the types of code mixing used in Aneka Yess! magazine, especially in “Palls Issue” rubric. The design of this study was descriptive qualitative. The techniques of data collection were: 1) collected the magazine during a month which consisted of two editions, namely 14 – 27 March dition, and 28 March – 10 April edition, 2) decided the rubric as an object of the study, 3) read the rubric, 4) underlined English code mixings, 5) identified the forms of code mixing. The result of this study showed that there were five forms of code mixings that used in the magazine, namely code mixing of word insertion that consist of 64 data, phrase insertion consist of 29 data, clause insertion consist of 10 data, reduplication insertion consist of 1 data, and idiom insertion consist of 4 data. The code mixings in word insertion was most frequently used in the magazine rather than the other types of code mixings, while the most rarely used was code mixing in reduplication insertion. It can be concluded that the using of code mixing was influenced by the capability or the knowledge of the speaker or interlocutor in using English language.